Design de formação continuada colaborativa: entre gestão escolar, tecnologias educacionais e metodologias ativas - Martins, Leandro Wendel (2023)
In-service continuing education refers to programs focused on the needs and interests of school communities which involve school professionals. This research aimed to design developmental collaborative actions of a culture of active methodologies and educational technologies implementation strategies through continuing online education of school managers. This study used a collaborative research-action methodology which allowed the shared design of the intentional propositions, divided into two stages: 1. In-service school managers continuing education on educational technologies and active methodologies. 2. Building of carried-out action plans to be offered to the teachers by their school managers. The research locus was the continuing education program, the interactions with Parana municipal education system during a school year, and the data produced and analyzed in two categories: 1. School managers continuing education program. 2. Selection of production from participating schools. The Systematic Literature Review (SLR) allowed the development of the theory that sustained the analysis of the content added to the literature selected by the researcher. The results made it possible to understand the educational technologies and active methodologies in-service continuing education process designed and developed with the school managers and the meaning of collaborative action design for group formations